2022
DOI: 10.3390/vaccines10020299
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Improved Psychological Distress (Anxiety and Depression Scores) in Chronic Kidney Disease Patients: A Prospective Study

Abstract: The purpose of the study is to analyze the impact of vaccination against SARS-CoV-2 on anxiety and depression scores in patients with different modalities of chronic kidney disease. One hundred and seventeen renal patients (50 hemodialysis patients, 13 peritoneal dialysis patients, 32 kidney transplants, and 22 advanced chronic kidney disease patients at pre-dialysis care) were evaluated for depression, anxiety, health-related quality of life (HRQOL), and perceived fears and resources with standardized (Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the poor health messaging, lockdowns, economic downturn, and poor management of the pandemic in early 2020 were also factors that could be expected to impact depression and anxiety symptoms. A prior study found that COVID-19 vaccination improved anxiety and depression in chronic kidney disease patients ( 9 ). However, in this study, depression and anxiety levels remained high in March 2021, despite the widespread availability of the vaccines that were shown to sharply decrease severe COVID-19, hospitalizations, and death ( 16 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the poor health messaging, lockdowns, economic downturn, and poor management of the pandemic in early 2020 were also factors that could be expected to impact depression and anxiety symptoms. A prior study found that COVID-19 vaccination improved anxiety and depression in chronic kidney disease patients ( 9 ). However, in this study, depression and anxiety levels remained high in March 2021, despite the widespread availability of the vaccines that were shown to sharply decrease severe COVID-19, hospitalizations, and death ( 16 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, few studies considered the impact of vaccine availability and whether it helps reduce mental stress. One study on chronic kidney disease patients found that COVID-19 vaccination improved anxiety and depression in this special group of patients ( 9 ). However, there is significant skepticism about COVID-19 vaccine and it is unknown whether the availability of vaccine improved mental health in the general public.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Spain by Carcia Liana et al, (2022), researchers investigated the impact of COVID-19 vaccination on anxiety and depression scores in patients with CKD. Results showed no significant differences for depression, anxiety, and health-related quality of life scores among the different groups of patients before and after vaccination[ 48 ]. Future studies should address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…It consists two subscales: anxiety subscale (HADS-A) and the depression subscale (HADS-D). The cut-off scores for the total score and subscales are as follows: a) 0–7 normal, b) 8–10 mild/doubtful, and c) >10 moderate-severe (clinical anxiety or depression)[ 25 ]. HADS Greek version has good psychometric properties and has proven useful to clinicians and health professionals for assessing anxiety and depression[ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in the case of fear of being infected in the pandemic, getting vaccinated may be a psychological resource to reduce anxiety and depression in the population. In a prospective study conducted by Garcia-Llana et al , it was observed that the depression score post-vaccination was significantly lower than the pre-vaccination score among patients with chronic kidney diseases 19. In December 2022, China reopened and moved to a new phase of COVID-19.…”
Section: Introductionmentioning
confidence: 99%